Deformation microstructures and textures, and regional tectonic significance of high-temperature shearing of the Diancang Shan Complex, Yunnan, China - Cao, S. Y.; Liu, J. L.; Leiss, B. (TRABAJOS DE GEOLOGÍA, 2009)
The Diancang Shan Complex located at the northwestern extension along the Ailao Shan-Red River (ASRR) shear zone is a representative metamorphic complex of the ASRR tectonic belt. This complex is constituted by two units, a central high-grade metamorphic belt and an eastern low-grade superposed metamorphic belt. Structural, microstructural, sub-microstructural and texture analysis of sheared rocks in the high-grade metamorphic rocks reveal that deformation of rocks occurred at high temperature conditions. The related structures, micro-structures and textures are attributed to left-lateral shearing along the ASRR shear zone, which also helps to constrain the timing of initiation of left-lateral shearing at early Oligocene.